An Analysis Of Language Learning Strategies Use - Dina Rachmawati (Bandar Lampung University (UBL), 2013)
The way people learn a language may be different from one person to another. The success of the students’ learning may be affected by the strategies which are employed by them. Moreover, in English department of Universitas Sultan Ageng Tirtayasa Serang Banten where the students are divided into two types of classes, regular and non-regular, it seems that the regular students perform higher academic achievement than the non-regular students. Therefore, attracted by the problem, this paper is aimed to investigate Language Learning Strategies (LLS) employ by the students. Strategy Inventory of Language Learning Strategies from Oxford (1990) was adopted as the main theory of the study.The subject of the research are second year students: regular and non-regular classes of English Department of UNTIRTA Serang Banten. It deals with how the students employ Language Learning Strategies in their study and the most frequently strategy used by the students. To collect the data, Questionnaire of SILL (Strategy Inventory of Langage Leearning) of Oxford (1990) was administered to the participants. The questionnaire consist of fifty statements which reflect the way language learners approach their language learning. Moreover, the stataments were classified into two major categories: cognitive and meta cognitive strategies. The questionnaire employed five Likert scale was used to show the tendency or the preference of LLS employed by the language learners.The study found that, firsly, generally the students employed Language Learning Strategies in Learning English. The students of regular class performed higher use of Language Learning Strategies than the non-regular students. Secondly, meta cognitive strategies, were frequently used the students, either the regular or the non-regular students. The study concludes that, all stundents regardless the level of their languge proficiency emloyed learning strategies. Moreover, academic performance seemed to be affected by the learning strategies employed by the students.